KULTUR PEMBELAJARAN GURU PKn SMP NEGERI DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Tuti Oktafiani; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out how the learning culture of State JuniorHigh School Civics teachers in Singingi District, Kuantan Singingi Regency. As for thepopulation and sample in this study are all of the State Junior High School Civicsteachers in Singingi District, Kuantan Singingi Regency were 12 people. By using totalsampling technique.. Data collection techniques used are through observation,questionnaires, interviews and documentation. In analyzing the data using quantitativedescriptive methods. The results of this study indicate that the learning culture of StateJunior High School Civics Teachers in Singingi Subdistrict, Kuantan Singingi Regencyruns very well. This is evidenced by the data from respondents that 21.73% answered